Foreign theories of regional management (Journal of Economic Research & Business Administration, 2016)
In the article are considered and systematized foreign theories of regional government. In recent years there was a number of scientific works on various problems of the theory of management in which authors differently open essence of concept «management» and its interrelation with the operated system. In article their content is disclosed, the main are defined, in particular spatial factors of growth and development, strong and weaknesses of these theories from a position of their adequacy to realities of the Kazakhstan reality. To create steadily growing economy, it is necessary to solve problems of decrease in interregional distinctions, to purposefully regulate their economic development. Thus, on growth and variety of regional problems considerable impact is exerted by such processes as formation of new geopolitical and economic space; economic crisis; emergence of new border regions with specific infrastructure, production, climatic problems, etc.
Keywords: regional management; region; theory of placement of the industry; theory of comparative advantages; theory of placement of production; theory of stages of growth; neoclassical theory; theory of cumulative causal relationships.